Wybrane zagadnienia zarządzania środowiskowego na przykładzie brytyjskich klubów piłkarskich = Selected aspects of environmental management on the example of British football clubs - Ceglińska, Marta (Journal of Education, Health and Sport, 2015)
Ceglińska Marta. Wybrane zagadnienia zarządzania środowiskowego na przykładzie brytyjskich klubów piłkarskich = Selected aspects of environmental management on the example of British football clubs. Journal of Education, Health and Sport. 2015;5(12):614-621. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44684 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A614-621 http://pbn.nauka.gov.pl/works/693611 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Ceglińska Marta. Wybrane zagadnienia zarządzania środowiskowego na przykładzie brytyjskich klubów piłkarskich = Selected aspects of environmental management on the example of British football clubs. Quality in Sport. 2015;1(4):7-17. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.12.2015. Revised 25.12.2015. Accepted: 29.12.2015. Marta Ceglińska Wydział Nauk Ekonomicznych i Zarządzania Uniwersytet Mikołaja Kopernika w Toruniu Wybrane zagadnienia zarządzania środowiskowego na przykładzie brytyjskich klubów piłkarskich Selected aspects of environmental management on the example of British football clubs Streszczenie Zarządzanie środowiskowe jest odpowiedzią na politykę ekologiczną państwa, zakładającą skuteczne i efektywne rozwiązywanie problemów środowiskowych na szczeblu lokalnym, regionalnym i krajowym (Karaszewski 2009). Jest to takie zarządzanie procesami w organizacji, aby minimalizować negatywny wpływ na środowisko. W niniejszym artykule przedstawiono wybrane zagadnienia z zakresu zarządzania środowiskowego w brytyjskich klubach piłkarskich. Wiele tamtejszych klubów sportowych już kilka lat temu mogło pochwalić się uzyskanymi certyfikatami z zakresu uwzględniania kwestii środowiskowych w swych działaniach. Słowa kluczowe: zarządzanie środowiskowe, systemy zarządzania środowiskowego, ISO 14001, EMAS, Forest Green Rovers, Manchester United Abstract Environmental management is a response to the state environmental policy, assuming an effective and efficient solution of environmental problems at the local, regional and national level (Karaszewski 2009). This is such a process management in an organization to minimize the negative impact on the environment. In this article, will be presented the issue of environmental management from the point of view of British football clubs. Many of them a few years ago boasted about certificates in the field of integration of the environment in their activities. Keywords: environmental management, environmental management systems, ISO 14001, EMAS, Forest Green Rovers, Manchester United